A Feasibility study on a Day Care Center for the Elderly - Alaan, Ailene B. (College of Engineering, 1995)
This project feasibility study concerns a day care center for our elderly people. The study presents an intensive market, technical and financial study, a socio-profitability as well as an implementation plan to provide a thorough analysis on the over-all requirements of establishing the day care center. All pertinent data re provided in this report and the highlights are as follows: In the course of the market study, a pre-feasiblity study was initially done in order to determine if there is indeed a demand for some special facility such as a home for the elderly that would suit their needs. Through the various surveys made, it was determined that the probability of producing a successful geriatric home is not a widely accepted idea for Filipinos who highly value close family ties and other associated cultural values. Thus, by coming up with a more popular alternative the concept of a day care center for the elderly came about, that is the FERALCA Day Care Center for the Elderly. The name for this center was named as such because it is representative of the proponents of the group who conducted this feasibility study i.e Fernandez, Alaan and Carlos, which is likewise easy to recall. The complete project name is descriptive of the type of service offered by the establishment. According to both statistics obtained from the National Statistics Office and the survey done, a large percentage of the market class targeted by this study of the elderly is located in the National Capital Region. The day care center would then offer them a variety of services, namely: Geriatric Consult and Financial Assessment, Rehabilitation Consult, Occupational Therapy, Memory Training Exercises, and a variety of activities which the elderly can enjoy. The experience itself can give them a better perspective in living in their golden years especially through socializing with their co-enrollees. The personal approach, numerous referrals and advertisements in the form of posters and brochures are the main marketing tools utilized to ensure a steady clientele for the center. The technical aspect of this study reveals that through the point-rating system done with reference to market study, the Center will be best located in Scout Chuatoco corner Panay Ave. Quezon City. This is where the elderly clients can undergo enrollment procedures in order to avail of the variety of services being offered by FERALCA. And in order to come p with the appropriate costs for all the materials to be used, several visits to different stores, government offices and also through phone calls the unit prices for the items required, the building, land and other labor costs were determined. These are particularly useful in determining the marked-up asking fee from each enrollee, and likewise the financial part of this study. Thus, a minimum fee of P 3,000.00 per 8 sessions consumable per month is charged per client. Meals will be provided throughout their daily stay at the day care. This fee to be charged per client determines a relative payback period of 6 years after a total project investment worth P 14,553,593. Several sources of financing the project were considered. The values incurred after the preparation of the different financial statements were then used in the financial analysis conducted to determine the viability of the project obtained unsatisfactory results. But it was observed after a projection of 5 years that the outcome was relatively improving at a fast rate. This increases the desirability of the project as an investment especially when the fact that any P3000 is being charged per client. In order to maximize the potential of FERALCA Day Care Center a number of well sought long-term plans were similarly devised. These are in the form of membership programs, a selection of packages of sessions and full blown advertising strategy. In turn, socio-profitability enumerates the benefits, dis-benefits, total costs and savings incurred upon establishment of the Center.